Sprowadź ułamki do wspólnego mianownika i oblicz podaną sumę. Wynik przedstaw w najprostszej postaci. a) [latex] frac{2}{5} + frac{11}{15} = frac{-}{-} + frac{-}{-} = frac{-}{-} = - frac{-}{-}[/latex] b) [latex] frac{7}{14} + frac{7}{21} = frac{-}{-} +
Sprowadź ułamki do wspólnego mianownika i oblicz podaną sumę. Wynik przedstaw w najprostszej postaci.
a) [latex] frac{2}{5} + frac{11}{15} = frac{-}{-} + frac{-}{-} = frac{-}{-} = - frac{-}{-}[/latex]
b) [latex] frac{7}{14} + frac{7}{21} = frac{-}{-} + frac{-}{-} = frac{-}{-} = - frac{-}{-} [/latex]
c) [latex] frac{3}{4} + frac{11}{16} = frac{-}{-} + frac{-}{-} = frac{-}{-} = - frac{-}{-} [/latex]
d) [latex] frac{8}{9} + frac{4}{7} = frac{-}{-} + frac{-}{-} = frac{-}{-} = - frac{-}{-} [/latex]